Hadith #5174 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Amr bin Abi Sufyan bin 'Abdur Rahman عمرو بن أبي سفيان بن عبد الرحمن; Ibn Jurayj ابن جريج; Kulda bin al-Hanbal; Muhammad bin Bashar Bindar محمد بن بشار بندار; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Yahya bin Habib bin Arby يحيى بن حبيب بن عربي (Sunan Abi Dawud)
A man came. Uthman’s version has: Sa’d ibn AbuWaqqas came. He stood at the door. Uthman’s version has: (He stood) facing the door. The Prophet (ﷺ) said to him: Away from it, (stand) this side or that side. Asking permission is meant to escape from the look of an eye.
Grade: Sahih